First observation of low energy electron neutrinos in a liquid argon time projection chamber - Acciarri, R.; Adams, C.; Asaadi, J.; Baller, B.; Bolton, Timothy; Bromberg, C.; Cavanna, F.; Church, E.; Edmunds, D.; Ereditato, A.; Farooq, Saima; Fitzpatrick, R. S.; et al. (My University, 2017)
The capabilities of liquid argon time projection chambers (LArTPCs) to reconstruct the spatial and calorimetric information of neutrino events have made them the detectors of choice in a number of experiments, specifically those looking to observe electron neutrino (nu(e)) appearance. The LArTPC promises excellent background rejection capabilities, especially in this "golden" channel for both short and long baseline neutrino oscillation experiments. We present the first experimental observation of electron neutrinos and antineutrinos in the ArgoNeut LArTPC, in the energy range relevant to DUNE and the Fermilab Short Baseline Neutrino Program. We have selected 37 electron candidate events and 274 gamma candidate events, and measured an 80% purity of electrons based on a topological selection. Additionally, we present a separation of electrons from gammas using calorimetric energy deposition, demonstrating further separation of electrons from background gammas.
Citation: Acciarri, R., Adams, C., Asaadi, J., Baller, B., Bolton, T., Bromberg, C., . . . ArgoNeu, T. C. (2017). First observation of low energy electron neutrinos in a liquid argon time projection chamber. Physical Review D, 95(7), 15. doi:10.1103/PhysRevD.95.072005
Keywords: Search; Beam; Astronomy & Astrophysics; Physics